HIGH SENSITIVITY CRP TO ALBUMIN RATIO IN PREDICTING THE MAJOR ADVERSE CARDIOVASCULAR EVENTS IN ACUTE CORONARY SYNDROME AT PRESENTATION (The Research of Medical Science Review, 2025)
Background: The C-reactive protein (CRP) to albumin ratio (CAR) has been identified as a potential indicator of inflammation and oxidative stress. High levels of inflammatory markers are frequently observed in patients with (ACS) and represent a marker of such condition's severity. Purpose: This study aimed to evaluate the prognostic role of (hs-CRP) to albumin ratio in predicting (MACE) in patients with ACS. Methods: This prospective, observational study conducted in department of Cardiology at Shifa International Hospital from July 24 till Dec 24. A total of 116 patients male and female patients aging 18 years and above with the diagnosis of ACS, including unstable angina, (NSTEMI), and (STEMI) were included. Hs-CRP to albumin ratio (CAR) was determined. The patients were monitored for occurrence of MACE. CAR in MACE versus non-MACE group was compared. Results: The study included 116 patients diagnosed with (ACS) mean age of 58.7 ± 11.4 years male accounted for 68.1% of the study population Baseline characteristics showed that the MACE group (n=38) was older (62.1 ± 12.3 years) compared to the non-MACE group (55.9 ± 10.5 years, p = 0.032). The incidence of MACE was 44.8% in patients (Q4: CAR > 0.60) with the highest and 7.9% in those (Q1: CAR < 0.20, p < 0.001) with lowest quartile of CAR concentrations. Conclusion: Raised hs-CRP to albumin ratio is an independent and powerful predictive factor for (MACE) in patients with (ACS). Regular measurement at baseline may add to risk stratification and assist clinical decision making in this high-risk group.